Current Status and Prospects of Spontaneous Peritonitis in Patients with Cirrhosis. (7th July 2020) - Li, Yong-Tao; Huang, Jian-Rong; Peng, Mei-Lian
Abstract : Spontaneous bacterial peritonitis (SBP) is a common cirrhotic ascites complication which exacerbates the patient's condition. SBP is caused by gram-negative bacilli and, to a lesser extent, gram-positive cocci. Hospital-acquired infections show higher levels of drug-resistant bacteria. Geographical location influences pathogenic bacteria distribution; therefore, different hospitals in the same country record different bacteria strains. Intestinal changes and a weak immune system in patients with liver cirrhosis lead to bacterial translocation thus causing SBP. Early diagnosis and timely treatment are important in SBP management. When the treatment effect is not effective, other rare pathogens should be explored.